eCITRA 2016: ‘Qualisigns’ art exhibition by Faculty of Applied and Creative Arts, UNIMAS - Rafee, Y.M (2016)
This year’s exhibition carries the theme, ‘Qualisigns: Exploring Semiotic Through Art Making’ and the art pieces will include paintings, sculptures, mix media, digital arts, ceramics and art installations. The faculty will be showcasing 45 art pieces by its academic staff at the Exhibition of Creativity, Innovation, Technology and Research in the Arts (eCitra) at Sabah Art Gallery from Oct 24 – Nov 17.